2013
DOI: 10.1186/1559-4106-8-15
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sample preparation methods of NIH/3T3 fibroblasts for ToF-SIMS analysis

Abstract: The information that is obtained from single cells during ToF-SIMS analysis is influenced by the method that was used to prepare the cells. The removal of extracellular media before analysis is necessary, but the rinsing technique should not damage the plasma membrane of the cell. The presence of intracellular salts reduced the secondary ion yield an average of 2.6-fold during Bi3+/C60++ depth profiles. Chemical fixation followed by rinsing removed a majority of the intracellular salts, “recovering” the positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 60 publications
(91 reference statements)
0
31
0
Order By: Relevance
“…Robinson and Castner compared different preparations and had also a focus on depth profiles. 18 In comparison to freeze-drying, it was suggested that formaldehyde fixation does not remove any molecular species to an extent detectable via ToF-SIMS. Analysis of frozenhydrated samples showed increased yields for larger mass fragments.…”
Section: A Sample Preparation Techniques For Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…Robinson and Castner compared different preparations and had also a focus on depth profiles. 18 In comparison to freeze-drying, it was suggested that formaldehyde fixation does not remove any molecular species to an extent detectable via ToF-SIMS. Analysis of frozenhydrated samples showed increased yields for larger mass fragments.…”
Section: A Sample Preparation Techniques For Cellsmentioning
confidence: 99%
“…17,18,26,31,33 Usually, only some lipid fragments are considered 17,26,33 or the investigation was carried out only in the positive ion mode, 26,33 while important lipid fragments such as fatty acids can only be seen in the negative ion mode. 18 Published comparisons are not comprehensive, e.g., Robinson and Castner 18 only analyzed formalin fixed cells; fixation via glutaraldehyde and secondary fixation via osmium tetroxide was not considered, and parameters of the freeze-drying procedure remain unclear. In particular, fixation by osmium tetroxide should be tested, as it is a known procedure to stain and fix tissues for electron microscopy based on the fixation of unsaturated lipids 34,35 and it might prevent lipid extraction during sample preparation.…”
Section: A Sample Preparation Techniques For Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15][16] Studies have been carried out in a variety of areas including the analysis of cancer cells, [17][18][19] cancer tissues, 20,21 muscular dystrophy, 22,23 and drug permeation into skin. 24 Several groups have discussed sample preparation methods for cells [25][26][27][28] and tissues. 14,29 However, the use of ToF-SIMS is still currently in early stages of development for answering biologically related questions.…”
Section: Introductionmentioning
confidence: 99%